Writing as a teaching learning technique: an example in chemistry (molar solution) - Adolfo E. Obaya V; Carlos Osorio G; Yolanda Marina Vargas (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Techniques are needed to train students in "writing to learn"., whose main goal is to "learn to write". This work aims to exemplify how writing can be a teaching learning technique in an example in Chemistry to develop a correct understanding of the preparation of molar solutions in the laboratory. It is essential that this is carried out in the classroom in a way that develops the reflective, analytical and cognitive skills of students. All this within an environment with safety measures at work.